THE PURE THEORY OF PUBLIC JUSTIFICATION. Issue 2 (29th April 2016) - Wall, Steven
Abstract: The ideal of public justification holds, at a minimum, that the most fundamental political and legal institutions of a society must be publicly justified to each of its members. This essay proposes and defends a new account of this ideal. The account defended construes public justification as an ideal of rational justification, one that is grounded in the moral requirement to respect the rational agency of persons. The essay distinguishes two kinds of justifying reasons that bear on politics and shows how they inform the ideal of public justification. It also decouples public justification from contractualist political morality. The result is a novel account of public justification that departs markedly from how the ideal is commonly characterized, but shows how it retains its distinctiveness as an ideal of politics.